The ecological drivers of growth form evolution in flowering plants. (11th April 2022) - Klimeš, Adam; Šímová, Irena; Zizka, Alexander; Antonelli, Alexandre; Herben, Tomáš
Abstract: In flowering plants (angiosperms), the herbaceous habit has evolved repeatedly from the ancestral woody state and herbs evolved repeatedly back to woody plants. Yet, how common these transitions were and which ecological conditions promote the herbaceous habit is poorly known. Several hypotheses exist, postulating an advantage of the herbaceous growth form to better cope with frost, drought, fire and shade and in allowing a fast life strategy, but their evaluation has been hitherto limited and support equivocal. We aim to evaluate these hypotheses by testing the difference between woody plants and herbs for a set of variables related to these hypotheses. We compiled and integrated data for up to 21, 581 species representing 359 families from public databases. We estimated the minimum number of evolutionary transitions between both growth forms. We assembled data on frost, drought, fire and shade tolerances, clonality and specific leaf area and we tested individual hypotheses by comparing herbaceous and woody angiosperm growth forms globally and within selected biomes and clades using phylogenetic comparative analyses. We found 1656 evolutionary transitions from woody towards herbaceous growth form and 2111 transitions in the opposite direction. In agreement with our expectations, herbs were more tolerant to frost and shade than woody plants and had higher specific leaf area. However, the growth forms did not differ in their fire tolerance and clonality. Furthermore, contrary to our expectation, woody plants were more drought tolerant than herbs. The majority of the differences were robust to the choice of biome or clade. Synthesis . Both herbaceous and woody habits evolved many times making the evolution of growth forms a well‐replicated event and suggesting that conditions favourable for either of the growth forms emerge often and plants respond to them. Apart from standard explanation by low temperatures, the success of herbs was likely enabled also by biotic interactions—by their fast life strategy, which is beneficial in seasonal and early successional habitats, and by their ability to tolerate shade. Abstract : Both herbaceous and woody growth form evolved many times within angiosperms suggesting that conditions favourable for either of them emerge often and plants respond to these conditions. Apart from standard explanation by low temperatures, the success of herbs was likely enabled also by biotic interactions—by their fast life strategy, which is beneficial in seasonal and early successional habitats, and by their ability to tolerate shade.